General equilibrium with monopolistic firms and occasionally binding cash-in-advance constraints - Huw Dixon; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2010)
We show a simple way to introduce monopolistic competition in a general equilibrium model where prices are fully .exible, the velocity of money is variable and cash-in-advance (CIA) constraints occasionally bind.We establish the conditions under which money has real effects and demonstrate that an equilibrium that occurs at a binding CIA constraint is welfare inferior to any equilibrium that occurs at a nonbinding CIA constraint with the same level of technology. We argue that even though the probability of a binding CIA constraint can be increasing with money supply, under certain conditions, expansionary money supply is welfare improving.
Keywords: D43; E31; E41; E51; 330; cash-in-advance; general equilibrium; monopolistic competition; Monopolistischer Wettbewerb; Konditionen; Geldangebot; Allgemeines Gleichgewicht; Theorie